PELAKSANAAN PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA LET’S READ UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA KELAS III MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI MERTAN 01 TAHUN PELAJARAN 2025/2026 - Kardi, Nunung Wiradi; Mulyati, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of student engagement and learning outcomes of third-grade students in Indonesian Language at Mertan 01 Elementary School in the 2025/2026 Academic Year. The pre-survey results showed that out of 17 students, only 42% achieved the Target Achievement Completion Criteria (KKTP) of 75, while 58% of students had not yet completed it. Furthermore, the level of student engagement in learning was also still low, with only 47% of students classified as active. This condition was caused by the implementation of teacher-centered learning and the minimal use of innovative media, resulting in a monotonous and less engaging learning environment. To address these issues, Let's Read digital media was implemented as an effort to increase student engagement and learning outcomes. Let's Read is a digital literacy platform that provides illustrated and leveled reading materials according to the ability level of elementary school students. This research used the Classroom Action Research (CAR) method which was implemented in several cycles including planning, implementation, observation, and reflection. The research results show that the implementation of Let's Read media can increase student engagement in learning and significantly improve the percentage of students completing learning outcomes. Therefore, the use of Let's Read media is effective in improving the quality of Indonesian language learning in elementary schools, particularly in terms of student engagement and learning outcomes.